Effects of Misclassification and Temporal Change of Response in Food Frequency on Risk Ratio - Hashimoto, Shuji; Nakai, Satoshi; Tsubono, Yoshitaka; Nishino, Yoshikazu; Fukao, Akira; Hisamichi, Shigeru (Journal of Epidemiology, 1997)
Misclassification and temporal changes of food consumption frequencies were estimated under the statistical models with some assumptions, and their effects on risk ratios were evaluated. Food frequencies of 27 items in 214 subjects were doubly measured by a questionnaire with 2 weeks interval, and those in 326 subjects were measured in 1989, 1993 and 1994. Median of probabilities of misclassification in responses among 27 food items was estimated to be 0.12. Medians of proportions of persons whose responses in 1989 were different from those after 5 years, were calculated to be 35% with misclassification and 27% without misclassification. For the true risk ratio of 3, medians of the risk ratios of dietary habits during 5 years, based on food frequencies measured at 1989, were observed to be 2.2 in case of responses with misclassification, and 1.7 in case of responses with misclassification and temporal changes. These suggested that the risk ratios of food frequencies would be seriously affected by misclassification and temporal changes in responses. J Epidemiol, 1997 ; 7 : 153-159.